2023
DOI: 10.1038/s44221-023-00090-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting microplastic masses in river networks with high spatial resolution at country level

Abstract: Microplastics are a ubiquitous contaminant of natural waters, and a lot of field monitoring is currently performed. However, what is missing so far is a general understanding how emissions of microplastics are linked to environmental exposure, especially on larger geographic scales such as countries. Here we coupled a high-resolution microplastic release model with a fate model in rivers and lakes and parameterized it for Switzerland on a country scale to predict masses of microplastics in each river section f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
(117 reference statements)
0
19
0
Order By: Relevance
“…In summary, we estimated that about three-quarters of the input macroplastic emissions were retained through long-term accumulation in river environments. This contrasts with microplastic retention behavior, which was found to be dominated by lakes, e.g., refs and but is supported by field observation of macroplastic litter on river banks, e.g., refs .…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…In summary, we estimated that about three-quarters of the input macroplastic emissions were retained through long-term accumulation in river environments. This contrasts with microplastic retention behavior, which was found to be dominated by lakes, e.g., refs and but is supported by field observation of macroplastic litter on river banks, e.g., refs .…”
Section: Resultsmentioning
confidence: 74%
“…In contrast to our findings for microplastics, the mass of macroplastic transported via the Rhône River (about 50 kg year –1 , average discharge false( Q false) = 338 m 3 s –1 ) toward France was about in the same order magnitude than other rivers with much lower discharges, e.g., Inn (62 kg year –1 , Q = 20 m 3 s –1 ) or Breggia (155 kg year –1 , Q = 1.2 m 3 s –1 ). Additionally, we calculated that about 20% of macroplastic mass was categorized as “flow into unknown”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it elaborated the concept of MPs for the first time, which also triggered the rapid growth of microplastic research in environmental media [2]. Plastic debris in the environment is a growing pollution problem, and a large number of studies have shown that MPs are ubiquitous on the planet and in polar regions, seawater, rivers, lakes, urban water bodies, underground water bodies, soils, the Qinghai-Tibet Plateau [3][4][5][6], food [7], and organisms [8]. "Plastics-the Fast Facts 2023" reported that global rate production rose from 1.7 million tons in 1950 to 367 million tons in 2020, in addition to 403 million tons in 2 of 21 2022 due to the COVID-19 pandemic in 2019 [9].…”
Section: Introductionmentioning
confidence: 99%